SOCIO-PHILOSOPHICAL ANALYSIS OF ARTIFICIAL INTELLIGENCE: PROBLEMS AND SOLUTIONS (Conferencea, 2023)
The article analyzes the philosophical problems of artificial intelligence, the role of artificial intelligence, information, information and information technologies in the development of society, the analysis of information as a mechanism of social development, the solution of existing problems and future tasks in this field is presented.